Book review: Vesiculation and crystallization of magma: fundamentals of the volcanic eruption process, by Atsushi Toramaru, 2022. Springer [Advances in Volcanology]; xxxii + 427 pages;hardcover price €149.79, paperback price €149.79; eBookprice €117.69, ISBN 978-981-16-4208-1 - Scarpati, Claudio (Geologos, 2023)
Book review: Vesiculation and crystallization of magma: fundamentals of the volcanic eruption pro-cess, by Atsushi Toramaru, 2022. Springer [Advances in Volcanology]; xxxii + 427 pages;hardcover price €149.79, paperback price €149.79; eBookprice €117.69, ISBN 978-981-16-4208-1